CAT S60 smartphone as a portable wound care device in home care - Jarmo Alametsä (Finnish Social and Health Informatics Association, 2022)
The purpose of this work is to study the suitability of the CAT S60 smartphone with built-in thermal camera to be used in self and home care to detect the risk level of wound appearance in advance. The purpose was to clarify different conditions where thermal imaging might act as a resource in detecting changes in limb circulation before visual signs even occur. The purpose is to detect early incipient tissue damage in foot usually occur in diabetic patients. Thermal images were acquired from voluntary domesticated elderly people. Thermal pictures from limbs of 3 persons were studied in order to find thermal differences indicating possible changes in limb circulation. Noteworthy thermal differences between limbs were found in elderly people. A smartphone having built-in thermal camera enables to detect plantar and limb thermal differences with a sufficient accuracy. This may support home monitoring for elderly people and thus reduce foot ulcers and possible foot amputations due to earlier detection and identification of harmful changes in limb circulation. Earlier detection of circulatory insufficiency via thermal imaging makes possible for nurses to intervene and enable medical assistance.